Поклонение огню: роман (Первая русская гангстерская сага, 2005)
Экземпляры: ф.22 (2006) / Инвентарный номер: 49697 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: Б 43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL